Chromosomal Damage in Pigs from a Farm of Central Argentina - Genghini, Rosa (1997)
Chromosomal aberrations can spontaneously occur in low proportion in pigs, therefore, high frequencies indicate a possible exposure to genotoxic agents. It seems that an increase in chromosomal mutation rate has taken place, taking into account the prevalence of such agents in the general environment of swine populations. For this reason, Gustavsson (1990) advocated the urgent necessity to identify environmental mutagens and to verify their effect on pig health. Chromosomal damage induced by radiation and also by chemical mutagens in swine has already been reported by diiferent authors. McFee et al. (1970a, 1970b, 1971, 1972, 1973, 1974) studied chromosomal mutation rate in lymphocytes caused by neutrons and gamma rays. Fries and Strazinger (1982) analyzed the mutagenic eifect in pigs derived from X-irradiated semen, having as a main consequence a decrease of litter size due to an induction of chromosomal transiocations and inversions. Forster and Butler (1978) demonstrated an in vitro adverse eifect of halothane on pig lymphocyte chromosomes. Pig chromosomal damage induced by virus was reported by Lodja and Rubes (1977) who found that the Swine Fever lapinized live vaccine induced structural chromosomal aberrations as well as lymphocyte polyploidy on vaccinated pigs. Rubes (1987) suggested the routine examination of lymnhocyte chromosome to assess the environmental quality of pig farms which are exposed to pollution from difTerent substances such as aflatoxin Bl, biphenols, polychlorinates, DDT, lindane, mercury and cadmium. Rubes et al. (1992) used this analysis not only in pigs but also in other farm animais as a poliution-level indicator due to agricultural and industrial activities in the Czech Republic. About 3.6% of pig lymphocytes showed chromosomal damage in highly contaminated farms of that country. Several cases of chromosomal damage in pigs with reproductive problems from a farm located in Rio Cuarto surroundings, an important swine production region of central Argentina, are reported in the present paper.